Efflux transporters and tight junction expression changes in human gastrointestinal cell lines cultured in defined medium vs serum supplemented medium - Warrier, A.; Gunosewoyo, Hendra; Crowe, Andrew (Elsevier, 2018)
© 2018 Aims: Many gastrointestinal cell lines including Caco-2, LS174T and RKO require foetal calf serum (FCS) in culture medium. However, when isolating secreted product from conditioned medium (CM), after cell exposure to a trigger, it is better to remove FCS in the culture medium for identification of secreted products of interest. However, it is unknown whether defined medium adversely affects active efflux protein expression and tight junction formation. Materials and methods: Using different gastrointestinal cell lines chosen with different levels of efflux transporter expression, fully defined components, such as using transferrin, insulin, selenium and ethanolamine without FCS or with a reduced percentage of FCS (2%) were tested as an optimal choice for cell growth. In addition to morphological characteristics, the expression of the ABC efflux transporters, ABCB1 (P-glycoprotein [P-gp]), ABCC2 (multidrug resistance associated protein 2), ABCG2 (breast cancer resistance protein) and occludin was determined. Key findings: The cells required a minimum of 2% FCS for expression of transporters. Fully defined medium with no serum adversely affected the expression of transporters, especially P-gp. An important characteristic of Caco-2 cells is its ability to form tight junctions. Caco-2 did not form adequate tight junctions without 10% FCS added in the medium, as evidenced by low TEER values and reduced occluding immunohistochemistry. Significance: FCS is required for efflux protein expression and tight junction generation. Nevertheless, it is possible to use 5 fold less FCS which assists with low molecular weight secretion isolation. Passage number also contributes significantly to the presence of these transporters.